Survivor‐led guidelines for conducting trauma‐informed psychological therapy assessments: Development and modified Delphi study. (1st September 2022) - Sweeney, Angela; White, Sarah; Kelly, Katie; Faulkner, Alison; Papoulias, Stan; Gillard, Steve
Abstract: Background: Psychological therapy assessments are a key point at which a person is accepted into a service or referred on. There is evidence of service users experiencing harm, dropping out of services and potentially experiencing poor outcomes because of inadequate assessment practices. Approaches to assessment tend to be developed by individual services, with a lack of research identifying what makes a good assessment. Methods: This survivor‐led study, based in England, aimed to generate guidelines for conducting trauma‐informed psychological therapy assessments. The study was guided by a Service User Advisory Group and a Clinician Advisory Group. The study was conducted in three key stages: (i) identifying, modelling and drafting guideline content (ii) modified Delphi study and (iii) guideline finalization. Stage 1 was informed by literature reviews, qualitative research, data workshops with Advisory Groups and an expert consultation. Fifty‐nine people with relevant experiences then participated in a single‐stage modified Delphi (Stage 2). The guidelines were finalized through an analysis of Delphi open comments and a final expert consultation (Stage 3). Results: The guidelines evolved through each stage of the process, and all items were deemed important by >90% of Delphi participants. The final trauma‐informed guidelines contain eight principles, including 'focus on relationships', 'from systems to people' and 'healing environments'. Conclusions: Experiential knowledge was key in generating the guidelines and conceptualizing content, with a consequent focus on areas, such as recognizing power differentials, understanding oppression as trauma and the relational aspects of assessments. Future research should focus on guideline implementation and investigate whether this impacts service user dropout, engagement with therapy, and outcomes. Patient or Public Contribution: This study is an example of survivor research, with several authors, including the study lead, identifying as survivors. We consider the ways in which our identities as survivor researchers impacted the study findings.